A képeslap, mint a turizmusmarketing fontos eszköze; tájesztétikai vizsgálatok a Medves-térség területén - Karancsi, Zoltán; Horváth, Gergely; Kiss, Andrea (Közép-Európai Közlemények, 2009)
This study is aimed at investigating the role, that postcards with a view of an area might play in interpersonal communication in the 21st century, an age of the internet, digital televison and mobile phones. The study also attempts to find out to what extent local inhabitants, as well as visitors to our region draw on the service of sending postcards, and also, whether or not they are familiar with those postcards, that feature the natural and cultural sights of the given area. Eventually, by finding the relevant answers to these questions, the study aims at identifying the general role, postcards play in area management and tourism marketing.